Potential‐Induced Spin Changes in Fe/N/C Electrocatalysts Assessed by In Situ X‐ray Emission Spectroscopy. (12th April 2021) - Saveleva, Viktoriia A.; Ebner, Kathrin; Ni, Lingmei; Smolentsev, Grigory; Klose, Daniel; Zitolo, Andrea; Marelli, Elena; Li, Jingkun; Medarde, Marisa; Safonova, Olga V.; Nachtegaal, Maarten; Jaouen, Frédéric; et al.
Abstract: The commercial success of the electrochemical energy conversion technologies required for the decarbonization of the energy sector requires the replacement of the noble metal‐based electrocatalysts currently used in (co‐)electrolyzers and fuel cells with inexpensive, platinum‐group metal‐free analogs. Among these, Fe/N/C‐type catalysts display promising performances for the reduction of O2 or CO2, but their insufficient activity and stability jeopardize their implementation in such devices. To circumvent these issues, a better understanding of the local geometric and electronic structure of their catalytic active sites under reaction conditions is needed. Herein we shed light on the electronic structure of the molecular sites in two Fe/N/C catalysts by probing their average spin state with X‐ray emission spectroscopy (XES). Chiefly, our in situ XES measurements reveal for the first time the existence of reversible, potential‐induced spin state changes in these materials. Abstract : The needed improvements in the activity and stability of Fe/N/C‐based electrocatalysts for the reduction of oxygen or carbon dioxide require a better understanding of their active sites' structure and electronic properties. To this end, herein we have applied ex situ and in situ X‐ray emission spectroscopy to track the potential‐induced changes in the average spin state of these materials' molecular Fe‐N x sites.